2017
DOI: 10.1038/s41598-017-00332-3
|View full text |Cite
|
Sign up to set email alerts
|

Cross-beta nanostructures based on dinaphthylalanine Gd-conjugates loaded with doxorubicin

Abstract: Very recently we proposed novel di- and tetra-phenylalanine peptides derivatized with gadolinium complexes as potentials supramolecular diagnostic agents for applications in MRI (Magnetic Resonance Imaging). It was observed that in very short FF dipeptide building blocks, the propensity to aggregate decreases significantly after modification with bulky moiety such as Gd-complexes, thus limiting their potential as CAs. We hypothesized that the replacement of the Phe side chain with more extended aromatic groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 37 publications
(47 reference statements)
3
22
0
Order By: Relevance
“…The coupling reaction of Fmoc‐Ahoh‐OH was achieved directly in the solid phase by carbodiimide activation. This synthetic method, largely used to prepare short PEG conjugates with molecular weights of 350–800, allows the preparation of PEGylated conjugates with monodisperse profiles.…”
Section: Resultsmentioning
confidence: 99%
“…The coupling reaction of Fmoc‐Ahoh‐OH was achieved directly in the solid phase by carbodiimide activation. This synthetic method, largely used to prepare short PEG conjugates with molecular weights of 350–800, allows the preparation of PEGylated conjugates with monodisperse profiles.…”
Section: Resultsmentioning
confidence: 99%
“…A three‐dimensional model of W4 aggregates was generated following the procedure previously adopted for similar systems by Diaferia et al ,. The structure of the hexapeptide fragment KLVFFA embodied in the amyloid‐beta peptide II (Protein Data Bank entry 3OW9) was used to generate the monomer of the W4 peptide by replacing all side chains with Trp residues.…”
Section: Methodsmentioning
confidence: 99%
“…Besides the cases of natural polymers here reported, novel studies have been reported on other materials, for example aromatic peptide-based materials that exhibit spontaneous phenomena of supramolecular organization into ordered nanostructures [59][60][61]. Here, the knowledge of their inner molecular organization was correlated to the design of novel molecules with enhanced and tunable properties for drug delivery or contrast agents.…”
Section: Discussionmentioning
confidence: 92%